Association among total serum isomers of perfluorinated chemicals, glucose homeostasis, lipid profiles, serum protein and metabolic syndrome in adults: NHANES, 2013–2014. (January 2018) - Liu, Hui-Shan; Wen, Li-Li; Chu, Pei-Lun; Lin, Chien-Yu
Abstract: Perfluorinated chemicals (PFCs) have been used widely in consumer products manufacture. Recent in vitro as well as animal studies have found that there are different toxicity and pharmacokinetic profiles between isomers of perfluorooctanoic acid (PFOA) and/or perfluorooctane sulfonate (PFOS). However, the differential effects of linear or branched PFOA/PFOS isomers on human beings have never been reported. Herein, we examined 1871 adult subjects (age older than 18 years) from the National Health and Nutrition Examination Survey (NHANES) 2013–2014 to determine the association between the isomers of PFOA/PFOS and serum biochemistry profiles, including glucose, lipids, protein and components of metabolic syndrome (MS). The results showed that for PFOA, increased linear PFOA was associated with increases in total cholesterol, serum albumin and an enhancement of β cell function as well as a decrease in the serum globulin. Increased branched PFOA was significantly associated with increased fasting glucose. All isomers of PFOA were positively associated with high-density lipoprotein-cholesterol (HDL-C) and negatively associated with glycohemoglobin (HbA1C). The branched PFOS was positively associated with β cell function and inversely associated with serum globulin. Both linear and branched isomers of PFOS were positively associated with the total protein and albumin. The increased branched PFOA was associated with less HDL-C insufficiency defined by the National Cholesterol Education Program Third Adult Treatment Panel (NCEP-ATP III) MS criteria, whereas the increased concentrations of serum total and linear PFOS were associated with less hypertriglyceridemia by the NCEP-ATP III. In conclusion, serum isomers of PFOA and PFOS were associated with glucose homeostasis, serum protein as well as lipid profiles; they were also indicators of MS. This may suggest that there is a distinct difference in the toxicokinetics of the isomers of PFOA and PFOS. Further clinical and animal studies are warranted to clarify the putative causal relationships between isomers and biochemical alterations. Graphical abstract: N.B. The associations between a given isomer and respective biochemistry profiles were shown here. T-cho denotes total cholesterol, alb albumin, HDL high-density lipoprotein. Highlights: A nationally representative sample from the NHANES 2013–2014. First to analyze associations between PFC isomers and serum biochemistry profiles. Each PFC isomer exhibits a unique association with serum biochemistry parameters. Abstract : This national representative study demonstrates the associations between a given PFC isomer and respective biochemistry profiles.